Решите уравнение 3(2х-1)-2(6-3х)=5+(4-х)

полина2054 полина2054    1   27.05.2019 06:10    5

Ответы
Маруська246 Маруська246  23.06.2020 22:52
3(2х-1)-2(6-3х)=5+(4-х)
6x-3-12+6x=5+4-x
6x+6x+x=3+12+5+4
13x=24
x=24:13
x=\frac{24}{13}=1 \frac{11}{13}
ПОКАЗАТЬ ОТВЕТЫ
Экфолорд Экфолорд  23.06.2020 22:52
3(2х-1)-2(6-3х)=5+(4-х)
раскрываем все скобки.
6x-3-12+6x=5+4-x
затем переносим все что с Х в левую, остальное в правую
6х+6x+x=5+4+3+12
13x=24
x=\frac{24}{13}=1 \frac{11}{13}
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра